ACCOUNTING IN A FREE ECONOMY. - Yang, J. M. (The Accounting Review, 1959)
Abstract Since the beginning men have been engaged in producing things necessary for subsistence and have been confronted with the problem as to what things to produce and how to produce them. As soon as several persons combined their efforts in production, there has been the problem as to what each should do and how the product should be distributed among them. The order or condition under which men decide and carry on their activities with reference to production and distribution characterizes an economy. An economy is said to be free when the members of a community, each according to his ability and situation, freely make decisions and carry on economic activities. In a social economy production is undertaken mostly by separately organized business enterprises which constitute the cells of the entire economic organism of society. Individuals take part in these business enterprises in various specialized capacities. Production is no longer for the direct consumption of persons participating in each business enterprise, but for sale to consumers or to other business enterprises which in turn produce for final consumption.